2004
DOI: 10.1677/jme.1.01503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dihydrotestosterone on adipose tissue measured by serial analysis of gene expression

Abstract: Intra-abdominal fat accumulation is related to several diseases, especially diabetes and heart disease. Molecular mechanisms associated with this independent risk factor are not well established. Through the serial analysis of gene expression (SAGE) strategy, we have studied the transcriptomic effects of castration and dihydrotestosterone (DHT) in retroperitoneal adipose tissue of C57BL6 male mice. Approximately 50 000 SAGE tags were isolated in intact and gonadectomized mice, as well as 3 and 24 h after DHT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 44 publications
3
29
2
Order By: Relevance
“…Several studies suggested that DEAD box polypeptide 5 (Ddx5) (also referred to as p68 RNA helicase) is involved in organ/tissue differentiation, 39) and it was recently reported that expression of the Ddx5 gene in murine adipose tissues was increased by the administration of dihydrotestosterne. 40) SWI/SNF-related matrix-associated actindependent regulator of chromatin subfamily b member 1 (Smarcb1) belongs to SWI/SNF family, which posseses helicase and ATPase activities and is thought to regulate the transcription of certain genes by altering the chromatin structure around those genes. 41) It was also reported that expression of Smarcb1 was increased in human adipocytes compared with that in preadipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that DEAD box polypeptide 5 (Ddx5) (also referred to as p68 RNA helicase) is involved in organ/tissue differentiation, 39) and it was recently reported that expression of the Ddx5 gene in murine adipose tissues was increased by the administration of dihydrotestosterne. 40) SWI/SNF-related matrix-associated actindependent regulator of chromatin subfamily b member 1 (Smarcb1) belongs to SWI/SNF family, which posseses helicase and ATPase activities and is thought to regulate the transcription of certain genes by altering the chromatin structure around those genes. 41) It was also reported that expression of Smarcb1 was increased in human adipocytes compared with that in preadipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…46 Wound MMP-2 and MMP-9 activities on day 6 post-injury were reduced in castrated animals, suggesting that, following wounding, androgens stimulate local gelatinase activity. While few published data pertain to the regulation by androgens of MMP-9, the expression of MMP-2 was reported to be DHT-and (synthetic androgen) R1881-induced in adipose tissue 47 and LNCaP cells, respectively. 48 Moreover, this latter response is effected by binding of the activated androgen receptor to a pair of androgen-response elements within the MMP-2 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of androgens on gene transcription in adipose tissue from male mice has been previously examined by serial analysis of gene expression in one study (7). Although very informative, that approach did not consider temporal expression regulation in response to the hormone.…”
mentioning
confidence: 99%